The making of the Bible: from the first fragments to sacred scripture - Schmid, Konrad (Harvard University Press, 2021)
Cover -- Title Page -- Copyright -- Contents -- 1. What Is "the Bible"? -- 2. Scribal Culture -- 3. Emerging Judaism -- 4. Scripture in Judaism -- 5. Ancient Jewish Texts in Early Christianity -- 6. The Formation of the Christian Bible -- 7. The Jewish Bible, the Mishnah, and the Talmud -- 8. The Book of Books -- Abbreviations -- Notes -- Bibliography -- Acknowledgments -- Illustration Credits -- Scripture Index -- General Index.